Exploring Export Potential and Green Economic Practices in Archipelagic Regions - Salafin, Syarifatus; Afifah, Uswatun Nurul; Faradis, Royhan (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
The leading exports of the island provinces still rely on primary goods rather than derivative goods. The exploitation of nature continues to be a strategy for island regions to enhance economic growth, but this approach does not promote a sustainable economy. This research aims to further describe the export commodities that remain dominant in provinces with archipelagic topography and to examine in greater detail the impact of these export activities on environmental resilience. The research methodology employs panel data regression with the Environmental Quality Index (EQI) serving as the dependent variable. The analysis reveals that economic activities, particularly exports, collectively influence the EQI. Furthermore, the research findings indicate a tendency for a weak relationship between superior commodity export activities and labor absorption.